Trichuris trichiura egg extract proteome reveals potential diagnostic targets and immunomodulators. - Katalina Cruz; Antonio Marcilla; Patrick Kelly; Michel Vandenplas; Antonio Osuna; María Trelis (PLoS Neglected Tropical Diseases)
Embryonated eggs are the infectious developmental stage of Trichuris trichiura and are the primary stimulus for the immune system of the definitive host. The intestinal-dwelling T. trichiura affects an estimated 465 million people worldwide with an estimated global burden of disease of 640 000 DALYs (Disability Adjusted Life Years). In Latin America and the Caribbean, trichuriasis is the most prevalent soil transmitted helminthiasis in the region (12.3%; 95% CI). The adverse health consequences impair childhood school performance and reduce school attendance resulting in lower future wage-earning capacity. The accumulation of the long-term effects translates into poverty promoting sequelae and a cycle of impoverishment. Each infective T. trichiura egg carries the antigens needed to face the immune system with a wide variety of proteins present in the shell, larvae's surface, and the accompanying fluid that contains their excretions/secretions. We used a proteomic approach with tandem mass spectrometry to investigate the proteome of soluble non-embryonated egg extracts of T. trichiura obtained from naturally infected African green monkeys (Chlorocebus sabaeus). A total of 231 proteins were identified, 168 of them with known molecular functions. The proteome revealed common proteins families which are known to play roles in energy and metabolism; the cytoskeleton, muscle and motility; proteolysis; signaling; the stress response and detoxification; transcription and translation; and lipid binding and transport. In addition to the study of the T. trichiura non-embryonated egg proteome, the antigenic profile of the T. trichiura non-embryonated egg and female soluble proteins against serum antibodies from C. sabaeus naturally infected with trichuriasis was investigated. We used an immunoproteomic approach by Western blot and tandem mass spectrometry from the corresponding SDS-PAGE gels. Vitellogenin N and VWD and DUF1943 domain containing protein, poly-cysteine and histidine tailed protein isoform 2, heat shock protein 70, glyceraldehyde-3-phosphate dehydrogenase, actin, and enolase, were among the potential immunoactive proteins. To our knowledge, this is the first study on the T. trichiura non-embryonated egg proteome as a novel source of information on potential targets for immunodiagnostics and immunomodulators from a neglected tropical disease. This initial list of T. trichiura non-embryonated egg proteins (proteome and antigenic profile) can be used in future research on the immunobiology and pathogenesis of human trichuriasis and the treatment of human intestinal immune-related diseases.